2019
DOI: 10.1021/acs.chemmater.8b04800
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably Distinct Mechanical Flexibility in Three Structurally Similar Semiconducting Organic Crystals Studied by Nanoindentation and Molecular Dynamics

Abstract: Distinct macroscopic mechanical responses of the three crystals of naphthalene diimide derivatives, 1Me, 1Et, and 1nPr, studied here are very intriguing because their molecular structures are very similar, with the difference only in the alkyl chain length. Among the three crystals examined, 1Me shows highly plastic bending nature, 1Et shows elastic flexibility, and 1nPr is brittle. A detailed investigation by nanoindentation and molecular dynamics (MD) simulations allowed us to correlate their distinct mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 66 publications
2
107
0
Order By: Relevance
“…We also emphasize the importance of the dynamics of side-chains beyond phase transitions of molecular crystals, as previous works have shown that slight modulation of side-chains can lead to drastic differences in various properties, such as molecular packing 15 and mechanical properties. 38,39 In this work, we further investigate the hypothesis that sidechain rotation is a molecular design rule for cooperative transition and demonstrate that the polymorphic transition mechanism is sensitive to even a single atom substitution. From ditBu-BTBT that exhibits a cooperative transition, we substitute a single atom in the side-chain from carbon to silicon.…”
mentioning
confidence: 95%
“…We also emphasize the importance of the dynamics of side-chains beyond phase transitions of molecular crystals, as previous works have shown that slight modulation of side-chains can lead to drastic differences in various properties, such as molecular packing 15 and mechanical properties. 38,39 In this work, we further investigate the hypothesis that sidechain rotation is a molecular design rule for cooperative transition and demonstrate that the polymorphic transition mechanism is sensitive to even a single atom substitution. From ditBu-BTBT that exhibits a cooperative transition, we substitute a single atom in the side-chain from carbon to silicon.…”
mentioning
confidence: 95%
“…Vice versa, a corrugated molecular structure of celecoxib without any slip-planes and numerous weak interactions in orthogonal directions were suggested to be the reasons for exceptionally high elasticity of its needle singe crystals [176]. Flat naphthalene diimine derivatives were found to have comparable crystal packing governed by π...π stacking, similar crystal morphology, but exhibited various mechanical flexibility attributed to close packing or interlock of their terminal alkyl chains [177]. Investigation of sulfa drug crystals [178], co-crystals of vanillin isomers [179], and amino acids [180] demonstrated that H-bonded layered structures with orthogonal distribution of strong and weak interactions attain the feasibility of cleaving a crystal along a given crystallographic plane parallel with these robust synthons.Particularly, single crystals with molecular surfaces formed by hydrophobic interactions can be applied as clean surfaces for molecular beam epitaxy.…”
Section: Bfdh Morphology Predictionmentioning
confidence: 97%
“…Quantitative nanoindentation experiments were performed on the (100) face of the straight crystal to explore the accurate mechanical properties of the bending face. [42][43][44] The representative load (P) versus depth (h) curve is shown in Fig. 1d.…”
Section: Quantitative Measurement Of Mechanical Propertymentioning
confidence: 99%